2020
DOI: 10.1186/s12883-020-1598-6
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Cryptococcosis revealed by transverse myelitis in Immunocompetent patient: a case report and review of the literature

Abstract: Background: Transverse myelitis (TM) is due to inflammatory spinal cord injury with bilateral neurologic involvement, which is sensory, motor, or autonomic in nature. It may be associated with autoimmune disease, vaccination, intoxication and infections. The most common infection cause of TM is Coxsackie virus and Mycoplasma pneumoniae. The cryptococcosis is rare. We present the case of disseminated cryptococcosis revealed by transverse myelitis in an immunocompetent 55-year-old male patient. The literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…He was put on consolidation therapy and is currently on maintenance therapy and has completely recovered on follow up. Others’ studies ( 4 , 8 , 9 ) also showed that correct diagnosis and prompt treatment results in 90% of patients showing complete recovery. This highlights the notion that if there are clinical pointers toward an infective etiology in case of a LETM, one should rule out cryptococcus CNS infection as it is a treatable condition ( 18 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…He was put on consolidation therapy and is currently on maintenance therapy and has completely recovered on follow up. Others’ studies ( 4 , 8 , 9 ) also showed that correct diagnosis and prompt treatment results in 90% of patients showing complete recovery. This highlights the notion that if there are clinical pointers toward an infective etiology in case of a LETM, one should rule out cryptococcus CNS infection as it is a treatable condition ( 18 ).…”
Section: Discussionmentioning
confidence: 87%
“…Overall, in cases of cryptococcal myelitis the median duration of onset of symptoms prior to admission was 38 days (IQR 9.5, 90). In the three cases of LETM reported in literature the duration of symptoms was 5, 10, and 150 days, respectively, ( 4 , 8 , 9 ). In our case, the patient had a four-day history of weakness prior to admission.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation